IMPLEMENTATION OF ADULT LEARNING IN MAJELIS TAKLIM NURUL KUJANG CIMAHI - Rakhman, Anita (EMPOWERMENT : Jurnal Ilmiah Program Studi Pendidikan Luar Sekolah, 2018)
AbstractÂ For adults, learning is to relate how to direct himself, to ask questions and also search for the answers and one means the gathering of adults, to conduct learning in an effort to increase religious knowledge through the Majelis Taklim. Adult learning uses rules such as group conversations, problem solving and exchanging experiences. The purpose of this study is to describe adult learning in Majelis Taklim and to provide information about the implementation of recitation activities in the Majelis Taklim. This research used descriptive research through qualitative method, where the researcher gives an overview about the activity held in Majelis Taklim that is reading the holy quran activity held at Majelis Taklim Nurul Kujang Cimahi which the participants are soldier's wife unity within the Army. This study used a qualitative approach, because the field phenomenon is comprehensive, complex, and full of meaning. The results of this study showed that adults are more interested in learning everything that is directly related to their lives and adults are more enthusiastic to learn when driven by a strong motivation.Keywords: adult learning, majelis taklim.